Does teacher competence and commitment improve teacher's professionalism - Abu Siri; I. Wayan Supartha; I. P. G. Sukaatmadja; Agoes Ganesha Rahyuda (Cogent Business & Management, 2020)
This study aims to examine and analyze the role of teacher competence and commitment in supporting teacher performance. The study was conducted on professional teachers in Madrasah schools in all regencies/cities in Bali which total of 906 teachers. The number of samples was determined based on the Slovin formula at an error rate of 5%, obtained 277 teachers distributed proportionally in 9 districts/cities. Data collection is done by direct interview based on a questionnaire that has been prepared. The collected data is then processed by the SmartPLS 3.0 program. The results showed that teacher competence and commitment was significantly positive effect on the performance of professional teachers. The teacher's commitment acts as a mediator of teacher competence and professional teacher performance. These results provide information on how to increase teacher performance. It is necessary to support the improvement of the competence and commitment of teachers.
Keywords: 650; teacher competence; teacher commitment; teacher performance